PENGINTEGRASIAN STATISTIKA TERAPAN PADA PENYELESAIAN SKRIPSI: STUDI KASUS MAHASISWA POLITEKNIK - Jonathan Saputra; Tri Wulan Sari (EPIGRAM (e-journal), 2023)
Research at the Polytechnic, including thesis work by final year students, could be integrated with the applied statistics’ competencies. This research aims to analyze the integration of applied statistics in the thesis completion of polytechnic student. Research data were collected using scientific questionnaires and structured interviews. Simple linear regression analysis is used as the analyzing method towards research questionnaire’s data. The descriptive results show that the most integrated competency of applied statistics is research’s hypothetical testing, followed by developing research instruments, presenting demographic data, collecting data, and determining the population and sample. The results of simple linear regression analysis with hypothesis testing show that the integration of applied statistics has a positive and significant impact on thesis completion of polytechnic student. These results were reinforced by structured interviews, so that it was found that the positive and significant impact felt by students lay in the better management of their thesis after integrating applied statistics. So, it can be concluded that applied statistics can be more integrated by polytechnic students to improve the management and quality of thesis research.